Erratum - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1990)
Erratum for: – An experimental lithotripsy system for the study of shock wave effects (L. FILIPCZYŃSKI, J. ETIENNE, A. GRABOWSKA, T. WASZCZUK, H. KOWALSKI, M. GRYZINSKI, J. STANISŁAWSKI) – Acoustical shadow of a sphere immersed in water. I (L. FILIPCZYŃSKI, T. KUJAWSKA) – Perception aspects of a rule system for converting melodies from musical notation into sound (L. FRYDEN, J. SUNDBERG AND A. ASKENFELT)